The role of hospitals in strengthening primary health care in the Western Pacific - Louise Freijser; Peter Annear; Naveen Tenneti; Katherine Gilbert; Ogochukwu Chukwujekwu; Indrajit Hazarika; Ajay Mahal (The Lancet Regional Health. Western Pacific, 2023)
Summary: Despite the imperative to strengthen primary health care (PHC) to respond to demographic and epistemological transitions, and meet commitments to achieve universal health coverage, health systems remain hospital-centric with health resources largely concentrated in urban centres. This paper examines islands of innovation that demonstrate the role hospitals can play in influencing the provision of PHC. Drawing on the literature and country case studies from the Western Pacific region, we illustrate mechanisms used to unlock hospital resources to improve PHC, with the transition towards “systems-focused hospitals”. This paper identifies four “ideal types” of roles hospitals perform to strengthen PHC in different contexts. This provides a framework to inform health systems policy by examining existing and potential roles of hospitals to support the provision of frontline services and reorient health systems towards PHC.